An Integrated PMT-TAM Approach to Cybersecurity Awareness: Evidence from Sierra Leone’s Universities and Policy Lessons for Developing Nations (International Journal of Scientific Research and Management (IJSRM), 2025)
This study pioneers the first empirical integration of Protection Motivation Theory (PMT) and Technology Acceptance Model (TAM) in West African academia to analyze cybersecurity awareness among 1,000 students across 10 Sierra Leonean universities (5 government, 5 private) using PLS-SEM. The novel PMT-TAM framework addresses theoretical fragmentation in behavioral cybersecurity literature by demonstrating how institutional factors (TAM) compensate for cognitive limitations (PMT) in resource-constrained settings a dynamic previously unexplored in African contexts. Results reveal moderate overall awareness (M = 3.42/5) but critical gaps, with only 12% accurately identifying phishing attempts. Key findings show self-efficacy (β = 0.58) and institutional support (β = 0.49) as the strongest predictors of protective actions, while perceived severity had weaker impact (β = 0.35). A significant "usage-awareness gap" emerged, with 89% of students using the internet daily but lacking fundamental security knowledge. Private institutions outperformed government counterparts in training quality (4.12 vs. 3.56, p < 0.01) and tool adoption (68% vs. 41% VPN usage). Theoretically, the findings advance hybrid behavioral models by revealing context-specific mediation effects (63% of perceived severity’s impact mediated by self-efficacy). Practically, the study provides actionable policy benchmarks, including allocating 3% of university IT budgets to cybersecurity and establishing national training standards. These insights are critical for developing nations undergoing rapid digitalization with limited security education infrastructure.